What drives conditional cooperation in public good games? - Peter Katuščák; Tomáš Miklánek (Experimental Economics, 2022)
Extensive experimental research on public good games documents that many subjects are "conditional cooperators" in that they positively correlate their contribution with (their belief about) contributions of other subjects in their peer group. The goal of our study is to shed light on what preference and decision-making patterns drive this observed regularity. We consider reciprocity, conformity, inequality aversion and residual factors, such as confusion and anchoring, as potential explanations. Effects of these drivers are separated by varying how others' contributions are determined and the informational content of the conditioning variable across treatments. Assuming additive separability of the effects of the four drivers, we find that, of the average conditionally cooperative behavior, at least 40 percent is driven by residual factors. For the remainder, most is accounted for by inequality aversion, some by conformity and very little by reciprocity. These findings carry an important message for how to interpret conditional cooperation observed in the lab. We also discuss what these findings mean for understanding conditional cooperation in fundraising applications in the field.
Keywords: H41; C91; D64; 330; Conditional cooperation; Reciprocity; Conformity; Inequality aversion; Confusion; Anchoring